Biología experimental como estrategia didáctica para mejorar el aprendizaje por descubrimiento de los alumnos del 4to grado de la I.E Áreas Técnicas Manuel Segundo del Águila - Tafur Tafur, Maitery Luisa (2011)
The didactic strategy experimental biology this strategy happens as an alternative to the traditional teaching where it is heeded that the theory and the practice are unrelated in such sense he perrnitted the theory's development and the practice achieving thus a significant learning. This investigation's general objective was to improve the learning for discovery in intervening Biology area the didactic strategy's application experimental Bíology in the pupils of the fourth secondary- educational grade. Above-mentioned strategy has theoretic support in the theory of the learning for discovery of Bruner, Jean Piaget's Theory of genetic Ausubel constructivismo's significant leaming Supported in these theoretic proposals, himself hypothesized , than if we apply the Biology Experimental as didactic strategy, then Manuel Segundo will improve significantly the learning for discovery in the pupils of the fourth secondaryeducation grade in the biology area of the lnstitution Educational with Technical areas himself Eagle Velásquez- Rioja. The fact-finding design is quasi experimental with pre test, with two groups experimental and control. The sign was shaped for the students 27 of the group control and 28 of the experimental group. 1 develop strategy during a trimester achieving to validate our fact-finding hypothesis, according to demonstrates it the afterrnaths obtained product of the application of the statistical formulas ( he tries of the difference once was paired off using distribution T Student ) in order to the verification of the hypothesis, obtained a value once was calculated of and a tabular value of, accepting hypothesis alternates, meaning to than improve him significantly the leaming for discovery in the pupils of the fourth secondary- education grade after the didactic strategy's application Biology Experimental.